Academic Achievement and Emotional Education Using Music Learning in Spain - Marcenaro-Gutiérrez, Óscar David; Colacio Moyano, Ana; López-Agudo, Luis Alejandro (Wiley, 2025)
In the current research work, we intend to analyse the effect of music on developing students' academic performance, self-concept and emotional development. We work with experimental data gathered from an application of special music lessons atschools aimed at developing students' learning and at educating their emotions in the academic year 2018–2019. These musiclessons consisted of collective, cooperative, practical, and experiential musical activities. Our results show that this interventionhad a positive influence on students' emotional development; nevertheless, it does not seem to influence students' academicachievement or their self-concept.
Keywords: Rendimiento académico; Educación emocional; Musicoterapia; Academic performance; Emotional development; Experimental research; Music; Self-concept